The spirit of Springer : the real-life rescue of an orphaned orca - Abler, Amanda (Sasquatch Books, 2020)
"A heart-warming and true story about an orphaned orca named Springer who was found swimming alone in the Puget Sound in 2002. The book takes us on Springer's journey from being near starvation to rescued to then the challenges of her release, eventual adoption, and the start of her own family."--